A farewell to didanosine: harm reduction and cost savings by eliminating use of didanosine. (October 2015) - Dziuban, Eric J; Raizes, Elliot; Koumans, Emilia H
Didanosine (ddI) is a nucleoside reverse transcriptase inhibitor associated with adverse events and public health concerns which have diminished its place in HIV clinical practice, particularly in resource-rich settings. While international guidelines do not contain ddI-containing regimens in preferred first- or second-line antiretroviral therapy (ART), there is no guidance for management of patients currently on ddI. In 2012 at least 20 countries purchased a total of $1–2 million of ddI. Drug purchase data in that year show 3.2–10.3 times higher costs for ddI compared to lamivudine (3TC). Given issues of multiple toxicities, monitoring, drug interactions, inconvenience, and virologic efficacy, as well as cost and formulary concerns, national (including resource-limited setting) ART programmes should consider complete phase-out of ddI.